Prática de lutas na educação física escolar: concepção curricular e a voz de alunos do Ensino Fundamental I - Meneses, Renan de (2020)
This dissertation has the purpose analyze the curriculum design and the practice of fights in the discipline of physical education, according to the education policies and the students opinion from 5° year of Elementary School I (ESI) from a public municipal school of São Paulo. The study justify itself before your contextualization of actual excitation of the teacher of physical education of finding the broaching of the conception of fights I’m school environment like a strategy that integrate the meaning of the diversity of the curriculum, just as the consideration of the lack of knowledge, insecurity and the concern about the violence point. The research characterized from qualitative approach, using methodological procedure bibliographic research, analyze of documents and field research, with utilization by the focus group technique. This one involved five students from Elementary School I, having in mind the meaning of practicing the fights expressed in the statements. The theoretical background refer to conception about practice of fights finded in documents like: The National Curricular Parameters, National Commom Curricular Base and Curriculum of the city, physical education at school and fights. Stand out the production of: Apple (1989); Saviani (2013); Gimeno Sacristán (2013); Saul e Saul (2018); Freire (2017); Rufino e Darido (2015); Nunes e Medeiros (2017); Gomes (2010, 2014); Campos (2014); Avelar-Rosa e Figueiredo (2009, 2015); and others. The finalization of this research allow to identify the contribution about the reflection of the student about the conception of fights. Stands out: the conception that the Physical Education at School still lacks of diversified practice; there’s intention that the teacher challenge himself and allow that student voice be listened, making this, classes then can make difference about the construction in the point of social education